BNDES portfolio of corporate stakes and equity returns: drivers and impacts - Barbosa, Marx Weber Ferreira (2018)
We add to the discussion of National Bank of Economic and Social Development (BNDES) operations by measuring, through the estimation of unbalanced panel, the drivers of its portfolio of corporate stakes, where the average volume between 2012 and 2016 was US$31 billion. We also model whether BNDES, as a shareholder and agent on the board of directors and fiscal council of firms, is able to impact their equities returns in terms of gain, risk and performance measures. Although there is no significant impact from BNDES shareholding or its induction to the board of directors, its appointment to the fiscal council is relevant to both the impact on the Sharpe Index and the drawdown. This finding is unprecedented and interesting due to the timing of this impact: the appointment to the fiscal council undesirably causes a reduction in the Sharpe Index and an increase of the stock drawdown in the first year; however, we find a reversion in the following year, providing a better performance and a reduction of the cumulative loss of stocks of the respective firms.